EDUCATIONAL EQUALITY TOWARDS THE DEVELOPMENT OF SUPERIOR HUMAN RESOURCES IN PKBM (COMMUNITY LEARNING ACTIVITY CENTER) KH ASYIKIN - Usman Raidar; Imam Mahmud; Dewi Ayu Hidayati; Teuku Fahmi; Finna Fitri Ayu Adrianti (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
The research has a locus in the field of the urgency of equal access to higher education for santri who come from limited economic and educational backgrounds and inadequate facilities in obtaining proper education. Pondok Pesantren Darussa'adah KH Asyikin Bandar Lampung is a religious-based non-formal educational institution in supporting educational inclusion to create superior and competitive human resources. Through the package A, B and C equivalency education programmes run with the KH Asyikin Community Learning Activity Centre, the boarding school provides opportunities for santri who do not graduate from formal schools to obtain diplomas equivalent to elementary, junior high and high school, so that eventually many graduates are eligible to continue to college. In 2025, the reducation process for this success passed eight students from the boarding school to enter UIN Raden Intan Lampung through the academic achievement pathway. The research used a qualitative approach with data collection methods through participatory observation, in-depth interviews, and documentation of the activities carried out by PKBM KH Asyikin